Evaluation of Property Taxes and Their Impact on the Real Estate Market - Arif Setyo (Golden Ratio of Taxation Studies, 2024)
This qualitative study explores the impact of property taxes on the real estate market through a comprehensive literature review and thematic analysis. The research aims to elucidate the multifaceted dynamics of property taxation, focusing on its effects on property values, investment behavior, and local government finance. Adopting an exploratory and descriptive research design, the study systematically examines existing literature from diverse sources to uncover underlying themes and patterns related to property taxation. Data collection involves extensive review of scholarly articles, books, reports, and policy documents, employing snowball sampling techniques to enhance comprehensiveness. Thematic analysis is conducted to categorize and interpret key findings, including the capitalization effect of property taxes on property values, the role of tax incentives in stimulating investment, and the challenges posed by property tax dependence in local government finance. The study underscores the importance of considering contextual factors, such as market conditions and socio-economic dynamics, in understanding the complex relationship between property taxes and the real estate market. The findings have implications for policymakers, practitioners, and researchers, highlighting the need for targeted tax relief programs, innovative policy solutions, and interdisciplinary collaboration to address the challenges and opportunities associated with property taxation.